The influence of light regime on the growth data and pigment composition of the plant Gentiana lutea cultured in vitro - L. R. Hrytsak; A. I. Herts; N. V. Nuzhyna; M. M. Cryk; V. V. Shevchenko; N. M. Drobyk (Regulatory Mechanisms in Biosystems, 2018)
New technologies of reintroduction of plant species presuppose implementing both traditional and biotechnological methods for obtaining certain planting materials. However, plants cultivated in vitro exist in specific conditions that lead to changes in their structural and functional state. This explains why it is hard for them to adapt to ex vitro and in situ conditions. Therefore, there is a need for the development of a multistage method of cultivating in vitro plants that would make the influence on their adaptive mechanism in ex vitro and in situ conditions possible. One of its stages is the optimization of the light regime of cultivation which can both initiate the change of the state of the photosynthetic apparatus of plants and increase their bioproductivity stimulating the work of their protective system. This work studies changes in the morphogenesis, growth data and pigment composition of the rare species of Gentiana lutea L. of three populations in the Ukrainian Carpathian (mountains Pozhyzhevska and Sheshul-Pavlyk, plateau Lemska) in vitro focusing particularly on the cultivation light regime. The research has proved the inefficiency of using fluorescent lamps of daylight lamps (LD) type as source of illumination because the low intensity of luminous flux in the area of photosynthetically active radiation (PAR), as well as high proportion of wavelength of blue (400–500 nm) and green (500–600 nm) range in the spectrum cause specific reactions of photomorphogenesis, which, despite the high content of pigments in plastids, lead to poor development of root systems, stretching the stems, formation of small leaves with thin leaflet plate, generally low productivity and low adaptive potential of G. lutea plants to ex vitro and in situ conditions. Complement of cold white light lamps to the fluorescent lamps LD type in the ratio of 1 : 1 enables one to increase the intensity of illumination in the field of PAR and raise the fraction of wavelength of red range (600–700 nm). Such light conditions both improve the bio-productivity of G. lutea plants of all three populations cultured in vitro in comparison to the LD type regimen, reducing the content of chlorophyll b and carotenoids in light-harvesting complexes of photosystems and facilitate an increase in the microclonal multiplication factor without using higher concentrations of exogenous growth regulators,which significantly reduces the cost of the process of obtaining planting materials. It was proved that a combination of LD type lamps, cold white light lamps and phytolamps in the ratio 1 : 1 : 0.6 should be used on the final stages of preparation of the planting material of G. lutea before transferring it to ex vitro and in situ conditions. This relates to the fact that the increase of the wavelength of the red range results in the widening of the active surface of the leaves, rise in the content of photosynthetic pigments, and the noticeable growth of the aboveground and underground parts of the plants. The article assumes that the use of such illumination mode will ensure a faster transition of cultured in vitro G. lutea plants from heterotrophic to autotrophic nutrition, improving their adaptive potential and enabling easier adaptation to non-sterile ex vitro and in situ conditions.